2009
DOI: 10.1016/j.jvs.2008.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Risk and Prognostic Factors in Mesenteric Venous Thrombosis

Abstract: aortitis may contribute to the spectrum of aortic diseases, perhaps linking patients with Takayasu disease and the various subgroups of degenerative and genetically related TAAs. Epidemiology, Risk and Prognostic Factors in Mesenteric VenousThrombosis Acosta S, Alhadad A, Svensson P, et al. Br J Surg 2008;95:1245-1251 Conclusion: Mesenteric venous thrombosis (MVT) can be accurately diagnosed with portal venous-phase computed tomography (CT) scanning, and activated protein C resistance is associated with MVT.Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 0 publications
1
45
0
4
Order By: Relevance
“…[1] Acute thrombosis is associated with a bowel infarction in one-third of patients. [12] The primary aim of treatment must be to avoid the pathological process that leads to necrosis, and early diagnosis is required to avoid transmural gangrene, perforation, and peritonitis. [13] Following advances in radiologic imaging, as well as, increasing awareness of mesenteric venous thrombosis, early detection and medical treatment obviating surgical intervention became feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Acute thrombosis is associated with a bowel infarction in one-third of patients. [12] The primary aim of treatment must be to avoid the pathological process that leads to necrosis, and early diagnosis is required to avoid transmural gangrene, perforation, and peritonitis. [13] Following advances in radiologic imaging, as well as, increasing awareness of mesenteric venous thrombosis, early detection and medical treatment obviating surgical intervention became feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, autopsy studies have determined that abdominal cancer is present in 22% of cases and hepatic cirrhosis is present in 17%. [12,16] Anticoagulant therapy for venous thromboembolism was first demonstrated by Barritt and Jordan in 1960. [17] Their randomized study reported that if patients do not receive anticoagulant therapy, approximately 25% experience fatal recurrences and another 25% experience non-fatal recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Dentro de los posibles focos, se menciona la apendicitis como la causa más frecuente, las enfermedades inflamatorias intestinales como la enfermedad de Crohn, infecciones del tracto biliar, pancreatitis aguda necrotizante, la sepsis tras la cirugía abdominal, diverticulitis y la septicemia generalizada [4][5][6][7][8][13][14][15] . Como condiciones predisponentes están las trombofilias, estados congestivos (cirrosis, insuficiencia cardíaca), cualquier tipo de neoplasia, situaciones que deben investigarse en forma dirigida 16,17 . En cuanto a las complicaciones, pueden producirse abscesos hepáticos que pueden requerir de tratamiento antibiótico asociado a su drenaje 5,13,18 .…”
Section: Discussionunclassified
“…2,[5][6][7] The proportion of patients with idiopathic cases decreases with more extensive evaluation. 8 Malignancies including myeloproliferative neoplasms are the most common form of prothrombotic disorders associated with MVT.…”
Section: Incidence and Etiologymentioning
confidence: 99%